Life-long environmental enrichment counteracts spatial learning, reference and working memory deficits in middle-aged rats subjected to perinatal asphyxia - Galeano, Pablo; Blanco, Eduardo; Logica Tornatore, Tamara M. A.; Romero, Juan I.; Holubiec, Mariana I.; Rodríguez de Fonseca, Fernando; Capani, Francisco (Frontiers in Behavioral Neuroscience, 2015)
Continuous environmental stimulation induced by exposure to enriched environment (EE) has yielded cognitive benefits in different models of brain injury. Perinatal asphyxia results from a lack of oxygen supply to the fetus and is associated with long-lasting neurological deficits. However, the effects of EE in middle-aged rats suffering perinatal asphyxia are unknown. Therefore, the aim of the present study was to assess whether life-long exposure to EE could counteract the cognitive and behavioral alterations in middle-aged asphyctic rats. Experimental groups consisted of rats born vaginally (CTL), by cesarean section (C+), or by C+ following 19 min of asphyxia at birth (PA). At weaning, rats were assigned to standard (SE) or enriched environment (EE) for 18 months. During the last month of housing, animals were submitted to a behavioral test battery including Elevated Plus Maze, Open Field, Novel Object Recognition and Morris water maze (MWM). Results showed that middle-aged asphyctic rats, reared in SE, exhibited an impaired performance in the spatial reference and working memory versions of the MWM. EE was able to counteract these cognitive impairments. Moreover, EE improved the spatial learning performance of middle-aged CTL and C+ rats. On the other hand, all groups reared in SE did not differ in locomotor activity and anxiety levels, while EE reduced locomotion and anxiety, regardless of birth condition. Recognition memory was altered neither by birth condition nor by housing environment. These results support the importance of environmental stimulation across the lifespan to prevent cognitive deficits induced by perinatal asphyxia.